Influência do ácido hialurônico na formação de filmes isolados de acetato polivinílico destinados ao revestimento de sólidos orais - Zanin, Giovane Douglas (2014)
The polyvinyl acetate is a polymer used in the development of formulations for sustained release of drugs. Hyaluronic acid (HA) can interact with receptors on the plasma membrane, especially CD44 that overexpressed in tumor cells. This paper presents a pre-formulation study of isolated polyvinyl acetate films with the addition of HA to the application perspective in pharmaceutical dosage forms destined to modified drug release. The films were prepared using the solvent evaporation method and evaluated according to macroscopic and morphologic characteristics, thickness, Fourier transform infrared spectroscopy (FTIR), thermal analyses (thermogravimetry and differential scanning calorimetry), scanning electron microscopy, water vapor transmission, and swelling index. Addition of HA enabled the formation of isolated films, influencing transparency, flexibility, and thickness. FTIR spectra demonstrated that only physical mixing occurred. TG and DSC curves indicated that films are thermally stable up to 200C. Electron micrographs showed modifications in the polymer mesh structure in samples (85:15 and 80:20) previously immersed in simulated gastric fluid and more pronounced after immersion in simulated intestinal fluid. The HA concentration also influenced water vapor permeability and swelling increasing these indices. We propose that films with 95:05 and 90:10 compositions can be used for modified drug release, as they were similar to a reference film and maintained targeted delivery.